2016
DOI: 10.1038/srep30028
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-induced perturbations in gut microbial diversity influences neuro-inflammation and amyloidosis in a murine model of Alzheimer’s disease

Abstract: Severe amyloidosis and plaque-localized neuro-inflammation are key pathological features of Alzheimer’s disease (AD). In addition to astrocyte and microglial reactivity, emerging evidence suggests a role of gut microbiota in regulating innate immunity and influencing brain function. Here, we examine the role of the host microbiome in regulating amyloidosis in the APPSWE/PS1ΔE9 mouse model of AD. We show that prolonged shifts in gut microbial composition and diversity induced by long-term broad-spectrum combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
428
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 528 publications
(456 citation statements)
references
References 56 publications
26
428
0
2
Order By: Relevance
“…At the same time, the onset of AD also supports the "hygiene hypothesis". Most recently, a new published study reported that antibiotic-induced perturbations in gut microbial diversity influenced neuro-inflammation and decreased A plaque deposition in a murine model of AD (Minter et al, 2016). All of these results demonstrate the pathology of AD may be associated with disturbance of gut microbiota.…”
Section: Resultsmentioning
confidence: 67%
“…At the same time, the onset of AD also supports the "hygiene hypothesis". Most recently, a new published study reported that antibiotic-induced perturbations in gut microbial diversity influenced neuro-inflammation and decreased A plaque deposition in a murine model of AD (Minter et al, 2016). All of these results demonstrate the pathology of AD may be associated with disturbance of gut microbiota.…”
Section: Resultsmentioning
confidence: 67%
“…The protective effects of autophagy and the proteasome are not specific to synuclienopathies, and the ability of the microbiota to modulate these critical cellular functions suggests that other amyloid disorders, such as Alzheimer's and Huntington's diseases, may be impacted by gut bacteria. In fact, recent studies have implicated the gut microbiota in promoting amyloid beta pathology in a model of Alzheimer's disease (Minter et al, 2016). Though we have explored postnatal effects of the microbiota in a model of neurodegenerative disease, our findings do not address the likely important role of microbial signals during prenatal neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of AD, antibiotic treatment decreases Aβ plaque deposition (Minter et al, 2016) and germ‐free APP transgenic mice have a drastic reduction in cerebral Aβ amyloid pathology (Harach et al, 2017). Poor dental status has been linked to AD or early signs of AD (Gatz et al, 2006).…”
Section: Systems Level Events In Aging and Admentioning
confidence: 99%